Robust circuit rhythms in small circuits arise from variable circuit components and mechanisms. (April 2015) - Marder, Eve; Goeritz, Marie L; Otopalik, Adriane G
Highlights: Analysis of small oscillatory circuits reveals variability in system parameters. Circuits with different parameter sets can be robust to moderate perturbations. Circuits with different parameter sets can be distinguished by extreme perturbations. Correlations in conductance expression can arise from homeostatic tuning rules. Degenerate circuit mechanisms can produce similar switches in circuit behavior. Abstract : Small central pattern generating circuits found in invertebrates have significant advantages for the study of the circuit mechanisms that generate brain rhythms. Experimental and computational studies of small oscillatory circuits reveal that similar rhythms can arise from disparate mechanisms. Animal-to-animal variation in the properties of single neurons and synapses may underly robust circuit performance, and can be revealed by perturbations. Neuromodulation can produce altered circuit performance but also ensure reliable circuit function.